2020
DOI: 10.3389/fgene.2020.00071
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Multigene Biomarker for Shrimp White Feces Syndrome by Full-Length Transcriptome Sequencing

Abstract: The pacific white shrimp, Litopenaeus vannamei, with the largest shrimp industry production in the world, is currently threatened by a severe disease, white feces syndrome (WFS), which cause devastating losses globally, while its causal agents remain largely unknown. Herein, compared to the Control shrimp by metagenomic analysis, we firstly investigated that the altered functions of intestinal microbial community in WFS shrimp were the enrichment of bacterial chemotaxis and flagellar assembly pathways, hinting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Aquaculture remains an important source of food and nutrition for millions of people worldwide, which plays an essential role in meeting the urgent global food demand (Low et al 2017 ). Pacific white shrimp, Litopenaeus vannamei , with the largest production in global shrimp industry, has suffered enormous economic losses due to serious infectious diseases (Zeng et al 2020 ). Diseases caused by viruses and bacteria have been major impact on the sustainable development of the industry, especially the occurrence of white spot syndrome virus (WSSV) (Tassanakajon et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquaculture remains an important source of food and nutrition for millions of people worldwide, which plays an essential role in meeting the urgent global food demand (Low et al 2017 ). Pacific white shrimp, Litopenaeus vannamei , with the largest production in global shrimp industry, has suffered enormous economic losses due to serious infectious diseases (Zeng et al 2020 ). Diseases caused by viruses and bacteria have been major impact on the sustainable development of the industry, especially the occurrence of white spot syndrome virus (WSSV) (Tassanakajon et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diseases caused by viruses and bacteria have been major impact on the sustainable development of the industry, especially the occurrence of white spot syndrome virus (WSSV) (Tassanakajon et al 2018 ). Recently, newer diseases have emerged, such as early mortality syndrome (EMS), acute hepatopancreatic necrosis disease (AHPND) or hepatopancreas necrosis syndrome (HPNS) (Flegel 2019 ; Huang et al 2016 ), and white feces syndrome (WFS) (Huang et al 2020 ; Zeng et al 2020 ). These diseases occurred in many Asian countries including China, India, Indonesia, Thailand and Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…However, the frequent occurrence of shrimp bacterial diseases, such as early mortality syndrome (EMS), acute hepatopancreatic necrosis disease (AHPND), hepatopancreas necrosis syndrome (HPNS), and white feces syndrome (WFS), has led to enormous economic losses every year worldwide (Sriurairatana et al, 2014;Lee et al, 2015;Choi et al, 2016;Huang et al, 2016;Xiong et al, 2017). In fact, the occurrence of L. vannamei bacterial diseases is closely associated with the obvious shifts in host intestine microbiota (Zhu et al, 2016;Hou et al, 2018;Huang et al, 2020;Zeng et al, 2020). Salinity is a very important abiotic factor affecting the intestine bacterial signatures (Zhang et al, 2016) and health status (Ponce-Palafox et al, 1997) of L. vannamei.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, many transcriptome studies in different crustaceans have been reported. Recently, transcriptomic approach has been employed in shrimp to understand the correct chronological order of the immune response events (Soo et al 2019) and immune function of haemocytes during pathogen infection and to identify multigene biomarkers of a specific disease (Zeng et al 2020). However, as a wide range of physiological responses including biotic and abiotic stressors, moulting and reproduction modulate the crustacean immune system, application of transcriptomic study is required to understand host responses against varied stressors.…”
Section: Conclusion and Future Studiesmentioning
confidence: 99%